Biologie und Epidemiologie der Hormonersatztherapie - Biology and Epidemiology of Hormone Replacement Therapy Diskussionen zur Postmenopausalen Gesundheit - Discussions on Post-Menopausal Health - Lewis, M. A.; Dietel, M.; Scriba, P.; Raff, W.K.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2006)
Die Vor- und Nachteile der Hormonersatztherapie (HRT) werden von einer Expertengruppe hinsichtlich der epidemiologischen Beweislage diskutiert. Den Diskussionsschwerpunkt bildet jedoch die Problematik des Brustkrebsrisikos. Unter anderem wird gezeigt, dass die aus epidemiologischen Studien abgeleiteten Ergebnisse sich nicht mit den Wachstumseigenschaften dieser Tumoren decken, so dass weiterführende Bevölkerungsuntersuchungen unter Einbeziehung pathobiologischen Sachverstands notwendig erscheinen. The benefits and risks of hormone replacement therapy (HRT) are discussed by a group of experts with a view towards the evidence provided by recent epidemiological studies. Although all aspects of HRT indications and contra-indications are reviewed, the particular emphasis of this discussion is on breast cancer. Among other things, it is shown that the evidence on breast cancer provided in epidemiological studies does not match the growth characteristics of the tumours, and that further population research incorporating pathobiological assessments is required.
The Presentations -- to the Presentations -- Women Between Biology and Civilization -- Issues with the Term “Responsibility” -- Epidemiology of Selected Diseases in Women -- Pathogenesis of Histological Types of Endometrial Cancer -- Pathology of the Colon and Ovary -- The Progenitor Cell Concept of Proliferative Breast Disease -- Indication for HRT: Climacteric Complaints and Osteoporosis -- HRT and Cardiovascular Disease in Women -- The Million Women Study -- Paradigm Shift in Causal Thinking in Epidemiology -- Perception and Communication of Risk -- Some Thoughts After the Kloster Andechs Workshop, August 2003 -- The General Discussion -- Menopause and the HRT Risk — Benefit Equation: Status and Outlook -- Conclusions of the Kloster Andechs Workshop -- Workshop Consensus: The State of the Evidence.
Keywords: Gynecology .; Epidemiology; Oncology .; Pathology; Gynecology; Epidemiology; Oncology; Pathology